2014
DOI: 10.4236/ojopm.2014.41005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(APP-co-EGDMA) Particles Using Monomers Derived from Cashew Nut Shell Liquid for the Removal of Cr(III) from Aqueous Solutions

Abstract: This work was aimed at synthesizing Cashew Nut Shell Liquid (CNSL) based polymer particles for adsorption of Cr(III) ions from aqueous solutions. Natural CNSL was used as a starting material in synthesizing amino pentadecylphenols (APP). This was achieved through isolating anacardic acid from the CNSL via calcium anacardate procedure, followed by hydrogenation of the alkenyl side chains, and subsequently decarboxylating the product to form 3-pentadecylphenol, which was then nitrated and reduced to a mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…5-pentadecyl-2,4-diaminophenol and 3-pentadecyl-2,4,6-triaminophenol synthesized as reported somewhere else [6].…”
Section: Corrosion Inhibitormentioning
confidence: 85%
See 1 more Smart Citation
“…5-pentadecyl-2,4-diaminophenol and 3-pentadecyl-2,4,6-triaminophenol synthesized as reported somewhere else [6].…”
Section: Corrosion Inhibitormentioning
confidence: 85%
“…In an effort to synthesize poly(APP-co-EGDMA) [6], we recently reported modification of Cashw Nut Shell Liquid (CNSL) to form a mixture of amino pentadecylphenols (APPs), i.e. 5-pentadecyl-2,4-diaminophenol and 3-pentadecyl-2,4,6-triaminophenol.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 The extremely high correlation coefficients of the linearized Langmuir model suggested that possibly the predominant sorption step in this sorption process is a single surface reaction with constant activation energy. 31 For the Langmuir models, the maximal biosorption capacity of adsorbent (q max ) is a crucial indicator of the adsorption characteristic of algal adsorbent. The residue of PTE-15 had the highest Cd 2+ adsorption capacity of 36.101 mg g À1 , which can be used as an effective biosorbent for the removal of Cd.…”
Section: Equilibrium Modelingmentioning
confidence: 99%